Identificación y valoración de impactos ambientales generados por las actividades de la minería informal, en el Cerro Luicho del Distrito de Colta, Provincia de Paucar del Sara Sara, Ayacucho - Blanco Benavente, Erick Eduardo (2020)
The research work was been carried out in the department of Ayacucho, province of Paucar de Sara Sara, District of Colta - Cerro Luicho, from April 2018 to December 2019. The activities identified are: Provisional works, Drilling, Blasting, Extraction, Transport and Pallaqueo. The significant environmental impacts caused by the mining activity have been determined and assessed. Around 42 environmental impacts have been detected, 10 of which are significant: Alteration of soil quality due to incorrect provision of RRSS, Alteration of soil quality due to disposal of fecal remains, Alteration of soil quality due to domestic effluent discharges, Alteration of soil quality due to oil and grease discharges, Loss of vegetation cover due to clearing, driving away of wildlife by generation of noise, Alteration of air quality due to the generation of particulate material, Alteration of the natural landscape due to clearing, Loss of geomorphology and soil structure. Mitigation programs are proposed, fundamentally complemented by environmental education